2010
DOI: 10.1152/ajprenal.00307.2009
|View full text |Cite
|
Sign up to set email alerts
|

8-pCPT-cGMP stimulates αβγ-ENaC activity in oocytes as an external ligand requiring specific nucleotide moieties

Abstract: Epithelial sodium channels (ENaC) are regulated by protein kinase A, in addition to a broad spectrum of other protein kinases. It is not clear whether cGMP/PKG signaling might regulate ENaC activity. We examined the responses of alphabetagamma-ENaC channels expressed in Xenopus oocytes to 8-(4-chlorophenylthio)-cGMP (8-pCPT-cGMP), a cell-permeable cGMP analog. This compound stimulated human alphabetagamma-ENaC activity in a dose-dependent fashion, but cell-impermeable cGMP had no effect. Similar stimulatory ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…Our previous studies found that heterologous ENaC expressed in oocytes may not be regulated by PKG (19). In PKG-deficient cells, the extent of compound stimulation of ENaC was identical to those transfected with scramble siRNA.…”
Section: Cpt-cgmp Stimulates Abg But Not Dbg Enacmentioning
confidence: 90%
See 3 more Smart Citations
“…Our previous studies found that heterologous ENaC expressed in oocytes may not be regulated by PKG (19). In PKG-deficient cells, the extent of compound stimulation of ENaC was identical to those transfected with scramble siRNA.…”
Section: Cpt-cgmp Stimulates Abg But Not Dbg Enacmentioning
confidence: 90%
“…CPT-cGMP, but not parent cGMP, acutely activated human ENaC activity as an external ligand (19,26). The aim of this study was to examine whether CPT-cGMP could be used as a pharmaceutical strategy to up-regulate alveolar fluid clearance (AFC) via stimulating ENaC and its underlying mechanisms.…”
Section: Epithelial Namentioning
confidence: 99%
See 2 more Smart Citations
“…External amiloride analogs, cations, anions, nucleotides, serine proteases, and laminar shear stress inhibit or stimulate endogenous or exogenous ENaCs (5)(6)(7)(8)(9)(10)(11)(12). All of these extracellular regulators appear to directly alter the activity of ENaCs in plasma membranes rather than affect channel subunit trafficking (1).…”
mentioning
confidence: 99%